Shockwaves Inhibit Chondrogenic Differentiation of Human Mesenchymal Stem Cells in Association with Adenosine and A2B Receptors. Issue 1 (December 2017) - Tan, Lei; Zhao, Bin; Ge, Fu-Tao; Sun, Da-Hui; Yu, Tiecheng
Abstract Extracorporeal shockwave therapy (ESWT) has emerged as the important choice for the treatment of many orthopedic disorders. Our previous mechanistic studies suggest that ESWT promoted osteogenesis of human mesenchymal stem cells (hMSCs) through mechanisms that involve adenosine 5′-triphosphate (ATP) release. In this study, we investigated the effect of ESWT on chondrogenesis of hMSCs. We demonstrate that ESWT treatment caused a significant release of adenosine from hMSCs; ESWT treatment increased the levels of A2B receptor (A2BR) in hMSCs under 3-D culture conditions. ESWT, exogenous adenosine and specialized A2BR agonist suppressed hMSC chondrogenic differentiation through downregulating the expressions of aggrecan (ACAN), Collagen Type I alpha 2(COL1A2), Collagen Type II alpha 1(COL2A1), Sex-Determining Region YBox 9 (SOX9) and Sex-Determining Region YBox 6 (SOX6). Selective A2BR antagonists induced chondrogenic differentiation of hMSCs. This study indicated that shockwave therapy inhibits hMSC chondrogenic differentiation through or partially through regulation of adenosine release and activation of A2B receptor under 3-D culture conditions.